Role of Topical Travoprost in Non Syndromic (simple) Axial Myopia in Young Persons - Arshad Ali, Noman Ahmed, Munawar Ahmed, M. Arshad Mahmood, Aif Mansoor Ahmed Murtaza Sameen (Pakistan Journal of Ophthalmology, 2015)
Purpose: To evaluate the role of topical Travoprost 0.004% eye drops in reducing simple axial myopia in young patients. Material and Methods: This case and control study was conducted on 45 young patients of either sex from 18 to 25 years old, who were selected by independent random sampling technique. Patients having best corrected visual acuity of 6/6 in both eyes, axial length more than 24 mm, myopia of -1.0 D to -4.0 D, and intraocular pressure of 16 to 20 mm Hg were registered for the study. After informed consent, slit lamp examination of anterior and posterior segment was done. Intra-ocular pressure and axial length were measured. Travoprost .004% eye drops were used in one eye once daily in the evening for four months. The fellow eye was kept as control. Follow up was done every month up to six months. On each visit best corrected visual acuity, axial length, and IOP were examined. Any complaint or complication was also noted and results were compiled. Results: In these forty five patients reduction of myopia in treated eye was seen in 24 (53.33%), stabilization of myopia in 13 (28.88%), and increase in myopia was seen in 08(17.77%) patients. In these patients IOP 7.2445 mm Hg, axial length 0.2089 mm, and myopia -0.4444 D was reduced (P-value less than .05, as compared to fellow control eye where axial length and myopia increased by 0.1423 mm and -0.0478 D respectively. Despite IOP decreased by 1.0889 mm Hg. P-value was again less than .05. Temporary headache in 8 (17.77%), Conjunctival congestion in 16(35%) patients. Complication of darkening and lengthening of lashes were noted to variable degree in all treated eyes. Conclusions: Topical Travoprost 0.004% eye drops is effective in reducing axial myopia in young persons. Key words: Myopia, refraction, axial length, IOP, Travoprost eye drops, Young patients.